PROFILE OF UNILATERAL CATARACT IN PEDIATRIC PATIENTS: A 3 YEAR RETROSPECTIVE STUDY - Ulya, Lisana Himmatul; Ekowati, Liana (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective: Unilateral cataract presents from 19.6% to 55.5% of pediatric cataract. This condition is treatable, but delayed treatment may cause visual impairment. This study aims to understand characteristic of unilateral cataract in children. Methods: This study was descriptive review of patients aged 0-17 years old with unilateral cataract at Dr. Kariadi Hospital, Semarang. Data were collected from medical record of patients from January 2019 to December 2022.   Results: Sixty patients were included in this study, 56.7% of whom were male and 43.3% were female. The mean age at presentation is 71.50 ± 48.34 months with whitish eye being the most common main complaint (65%), followed by blurred vision (35%) and squinting of eye (5%). Most of patients had congenital or infantile cataract (60%), followed by traumatic (36.6%), uveitis (1.7%) and iatrogenic (1.7%). Some of patients had microcornea (21.7%), persistent pupillary membrane (8.3%), retinopathy of prematurity (3.3%), persistent fetal vasculature (8.3%), nystagmus (8.3%), amblyopia (20%) and strabismus (40%), with exotropia being the most common type (33.3%). Most of patients did not have systemic disease (93.3%), but we found two patients had congenital rubella syndrome, one had congenital cytomegalovirus, one had down syndrome. Conclusion: Etiology of unilateral pediatric cataract mostly idiopathic followed by traumatic. Leukocoria was the most common complaint, followed by blurred vision and strabismus. In unilateral cataract, exotropia was more common type of strabismus.